Implementation of Diplomatic Assurance Against Torture: The Way to Reduce the Refugee Crisis in South Asia - Chowdhury Nujhat Samanta; Mohammad Belayet Hossain (Lex Publica, 2022)
States aim to send refugees back to their home countries in order to end the refugee crisis in their nation. Due to the human rights situation in the countries of origin, this can occasionally be problematic; the return involves the prohibition of refoulment and the prevention of torture or other cruel treatment. States are not allowed to use torture, including putting someone in a position where they might be tortured. For a very long time, diplomatic guarantees have been employed as a defense against the death penalty or unfair trials. From that time, states used to rely on guarantees for a returnee’s treatment. The guarantees were protected at the diplomatic level of relations between nations. In this research, subject to legal value, the reliability of diplomatic assurance is measured as well as an assessment has been made about the current state of south Asian nations that have hosted refugees for an extended time. This paper also supports the use of diplomatic assurance as a workable option to alleviate the refugee crisis where developed countries can contribute the best. The findings indicate that there is no specific legal framework to support such assurances in different south Asian developing as well as other developed countries. There is even a lack of research in this regard. South Asian nations could take seven factors into account according to the recommendations of the study. So, it is necessary to implement the recommendations to reach the goal of solving the refugee situation. Abstrak Negara bertujuan untuk mengirim pengungsi kembali ke negara asal mereka untuk mengakhiri krisis pengungsi di negara mereka. Karena situasi hak asasi manusia di negara asal, hal ini terkadang menimbulkan masalah; pengembalian melibatkan larangan refoulment dan pencegahan penyiksaan atau perlakuan kejam lainnya. Negara tidak diperbolehkan menggunakan penyiksaan, termasuk menempatkan seseorang pada posisi di mana mereka mungkin disiksa. Untuk waktu yang sangat lama, jaminan diplomatik digunakan sebagai pembelaan terhadap hukuman mati atau pengadilan yang tidak adil. Sejak saat itu, negara biasanya mengandalkan jaminan untuk perawatan orang yang kembali. Jaminan tersebut dilindungi pada tingkat diplomatik hubungan antar negara. Dalam penelitian ini, tunduk pada nilai hukum, keandalan jaminan diplomatik diukur serta penilaian telah dibuat tentang keadaan negara-negara Asia Selatan saat ini yang telah lama menampung pengungsi. Tulisan ini juga mendukung penggunaan jaminan diplomasi sebagai opsi yang dapat diterapkan untuk mengurangi krisis pengungsi di mana negara maju dapat memberikan kontribusi terbaiknya. Temuan menunjukkan bahwa tidak ada kerangka hukum khusus untuk mendukung jaminan tersebut di berbagai negara berkembang Asia Selatan serta negara maju lainnya. Bahkan ada kekurangan penelitian dalam hal ini. Negara-negara Asia Selatan dapat mempertimbangkan tujuh faktor sesuai dengan rekomendasi penelitian. Jadi, perlu untuk menerapkan rekomendasi untuk mencapai tujuan penyelesaian situasi pengungsi. Kata kunci: Negara Asia Selatan, Pengungsi, Negara Maju, Jaminan Diplomatik